Challenging multiculturalism : European models of diversity - Taras, Ray, 1946-. (Edinburgh : Edinburgh University Press, 2013)
"In recent years, European political leaders from Angela Merkel to David Cameron have discarded the term 'multiculturalism' and now express scepticism, criticism and even hostility towards multicultural ways of organising their societies. Yet they are unprepared to reverse the diversity existing in their states. These contradictory choices have different political consequences in the countries examined in this book. The future of European liberalism is being played out as multicultural notions of belonging, inclusion, tolerance and the national home are brought into question."-- Publisher's website
Includes bibliographical references and index.
Keywords: Multiculturalism -- Europe